2007
DOI: 10.1111/j.1741-2358.2007.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of the elderly in a residential home in Turkey

Abstract: The results illustrated poor dental health and showed extremely high demand for the dental health services programmes for the elderly living in these institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 26 publications
11
40
3
1
Order By: Relevance
“…Some recent studies have shown that people in developing countries were found to have high caries prevalence for all age groups compared with developed countries (Bolin et al, 1996;Carvalho et al, 2001;Christensen et al, 2003;Gibson et al, 1999;Güçiz and Gökalp, 2008;Sheiham, 2005;Unlüer et al, 2007). According to those studies conducted in a developing country to estimate prevalence and severity of oral and dental health problem, more than half of the individuals had dental caries and the prevalence of normal population without a toothbrush was 15.9%, the toothbrushing rate 2 to 3 times daily was 22.2 and 27.6% in adults and geriatric peoples, respectively Güçiz and Gökalp, 2008;Unlüer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have shown that people in developing countries were found to have high caries prevalence for all age groups compared with developed countries (Bolin et al, 1996;Carvalho et al, 2001;Christensen et al, 2003;Gibson et al, 1999;Güçiz and Gökalp, 2008;Sheiham, 2005;Unlüer et al, 2007). According to those studies conducted in a developing country to estimate prevalence and severity of oral and dental health problem, more than half of the individuals had dental caries and the prevalence of normal population without a toothbrush was 15.9%, the toothbrushing rate 2 to 3 times daily was 22.2 and 27.6% in adults and geriatric peoples, respectively Güçiz and Gökalp, 2008;Unlüer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to those studies conducted in a developing country to estimate prevalence and severity of oral and dental health problem, more than half of the individuals had dental caries and the prevalence of normal population without a toothbrush was 15.9%, the toothbrushing rate 2 to 3 times daily was 22.2 and 27.6% in adults and geriatric peoples, respectively Güçiz and Gökalp, 2008;Unlüer et al, 2007). These results were quite similar to the results of a previous comprehensive study, which was carried out in the same country in 1988 with the support of the World Health Organization (WHO) (Saydam et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Studies about oral health attitudes and behavior in Turkey is limited with dental students 3,7,15 and elder population. 16 This study searched oral health attitudes and behavior of adults in a Turkish population. This study showed that females gave priority to medicine over clinical examination in the presence of toothache.…”
Section: Discussionmentioning
confidence: 99%
“…5 En Turquía el 32,6 % de los pacientes dentados presentaron 2,2 piezas con caries radiculares y el 20,7 % tenía al menos una lesión cariosa en corona no tratada. 6 En Chile 48.3 % era desdentado total y 51.7 % parcial, esto se distancia un poco de lo obtenido en adultos mayores de 60 años de nivel socioeconómico bajo en el norte de Santiago en los cuales el 25,9 % era desdentado total. 8 Las personas con un edad mayor de 81,8 años, presentaron una mayor pér-dida de piezas dentarias.…”
Section: 2unclassified